2007
DOI: 10.1111/j.1432-2277.2007.00556.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of immunoglobulin and mannose binding protein levels after renal transplantation: association with infectious complications

Abstract: Summary Hypogammaglobulinemia (hypo‐Ig) and low mannose binding protein (MBP) levels might be involved in the infectious risk in renal transplantation. In 152 kidney transplant recipients treated with calcineurin inhibitors (CNI) and mycophenolate mofetil (MMF), during the first year, we prospectively recorded the incidence of hypogammaglobulinemia, and low MBP levels. Their influence on infectious complications was evaluated in 92 patients at 3 and 12 months (T3 and T12). The proportion of deficiency increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
45
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 27 publications
9
45
1
Order By: Relevance
“…This effect of MMF on the humoral immunity was later observed in other types of SOT (27,28). Nevertheless, neither this study nor that of Broeders et al (15) found any significant association between the type of maintenance immunosuppression and the risk of HGG. It has been suggested that the decrease in helper T cell population after antirejection therapy may lead to acquired posttransplant HGG.…”
Section: Discussioncontrasting
confidence: 43%
See 4 more Smart Citations
“…This effect of MMF on the humoral immunity was later observed in other types of SOT (27,28). Nevertheless, neither this study nor that of Broeders et al (15) found any significant association between the type of maintenance immunosuppression and the risk of HGG. It has been suggested that the decrease in helper T cell population after antirejection therapy may lead to acquired posttransplant HGG.…”
Section: Discussioncontrasting
confidence: 43%
“…The presence of HGG of any class at month 1 was independently associated with the incidence of bacterial infection during the intermediate posttransplant period, whereas HGG at month 6 was associated with either overall infection or bacterial infection in the late period. The literature contains some studies aimed at assessing the incidence and relevance of HGG after KT (12)(13)(14)(15). Most of them, however, were performed more than a decade ago (12)(13)(14), thus limiting the validity of their findings in the setting of contemporary immunosuppressive and prophylactic practices, or were based on small sample sizes (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations